Carbon and nitrogen optimization in solid-state fermentation for sustainable sophorolipid production using industrial waste - Eras-Muñoz, Estefanía; Gea, Teresa; Font, Xavier (Frontiers in Bioengineering and Biotechnology, 2024)
The use of alternative feedstocks such as industrial or food waste is being explored for the sustainable production of sophorolipids (SLs). Microbial biosurfactants are mainly produced via submerged fermentation (SmF); however, solid-state fermentation (SSF) seems to be a promising alternative for using solid waste or byproducts that could not be exploited by SmF. Applying the advantages that SSF offers and with the aim of revalorizing industrial organic waste, the impact of carbon and nitrogen sources on the relationship between yeast growth and SL production was analyzed. The laboratory-scale system used winterization oil cake as the solid waste for a hydrophobic carbon source. Pure hydrophilic carbon (glucose) and nitrogen (urea) sources were used in a Box–Behnken statistical design of experiments at different ratios by applying the response surface methodology. Optimal conditions to maximize the production and productivity of diacetylated lactonic C18:1 were a glucose:nitrogen ratio of 181.7:1.43 (w w−1 based on the initial dry matter) at a fermentation time of 100 h, reaching 0.54 total gram of diacetylated lactonic C18:1 with a yield of 0.047 g per gram of initial dry mass. Moreover, time course fermentation under optimized conditions increased the SL crude extract and diacetylated lactonic C8:1 production by 22% and 30%, respectively, when compared to reference conditions. After optimization, industrial wastes were used to substitute pure substrates. Different industrial sludges, OFMSW hydrolysate, and sweet candy industry wastewater provided nitrogen, hydrophilic carbon, and micronutrients, respectively, allowing their use as alternative feedstocks. Sweet candy industry wastewater and cosmetic sludge are potential hydrophilic carbon and nitrogen sources, respectively, for sophorolipid production, achieving yields of approximately 70% when compared to the control group.